Identifying factors impact on investment in financial services under digital financial ecosystem transformation - Manoylenko, Oleksandr; Kuznetsova, Svitlana (Technology audit and production reserves, 2025)
The object of research is global investment processes in the financial services sector. The problem is the gaps in the development of analytical tools for assessing and forecasting the volume of global investments in the financial services sector when the role of financial institutions changes in the digital transformation of the financial ecosystem. Correlation-regression analysis methods serve as the methodological basis of this research, implemented on the basis of Oxford Economics statistical data. A theoretical analysis of scientific approaches has been conducted to identify potential key factors influencing investments in financial services. A sample of statistical data on the dynamics of the international capital market has been formulated, characterizing changes in indicators of the financial services sector for the period 2004–2024. A correlation analysis has been conducted to identify multicollinearity of the identified factors and the resulting indicator – investments in financial services to assess their density and direction of the relationship. As a result of modeling, a regression equation with high reliability has been obtained. The model showed that gross output (X1) acts as a dominant positive driver of investment activity. In turn, the most significant result is the detection of a statistically significant negative impact of the share of the financial sector in GDP (X4) on total investment in the sector. The main forecast scenarios of the dynamics of global investments in financial services are formulated. The multidirectional impact on the dynamics of investment processes is determined – scale and structural balance within the integrated model. The practical result of its implementation is the application of the proposed toolkit for making investment and regulatory decisions in the medium term by investment funds, fintech companies and financial market regulators.